Orange sweet potato flour production: Comparative effects on ultrasound, drying, storage, and techno-economic assessment - Analaura Gómez-Cisneros; Alberto Ordaz; Liliana Santos-Zea; Anayansi Escalante-Aburto; Edith Ponce-Alquicira; Mariel Calderón-Oliver (Applied Food Research)
Sweet potatoes (Ipomoea batatas) are recognized for their nutritional value and rich content of bioactive compounds, which contribute to their health benefits. Despite these advantages, the limited diversity of products derived from sweet potatoes has hindered their broader industrial application. This paper discusses the potential of transforming sweet potatoes into flour and explores the implications of drying processes on bioactive compound retention. Furthermore, it examines the efficacy of ultrasound as a method to enhance the extraction and preservation of these valuable compounds during processing. Therefore, this study aimed to evaluate the effects of 3 factors and their interaction: ultrasound treatment (40 kHz, 10 min at 25 °C), storage time after ultrasound (0–96 h), and drying methods (cabinet dehydration and freeze-drying) to obtain sweet potato flour without reducing bioactive compounds, color and antioxidant activity, as well as its techno-economic feasibility. Ultrasound treatment and drying processes mainly impact the final color, phenolic content, and carotenoids. Dehydration decreases the bioactive content compared to lyophilization; however, the ultrasound treatment causes an increase in concentration after 48 h of storage (53.8 % more than control without ultrasound). Also, dehydration increases the a* and b* levels in the final flours. Finally, the process was proposed to be scaled industrially using SuperPro Designer software. The techno-economic assessment demonstrated that obtaining flour through ultrasound and dehydration is both scalable and economically feasible, providing an industrial option for sweet potato commercialization.